Kegiatan layanan dalam penelusuran informasi di perpustakaan - fauzi eka putra (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
This article discusses about service activity in information tracking in the library is very important because it is one of the activities directly related to the user. Service activities are also a means of measuring the success of a library implementation. Library service activities are always directed and focused on how to provide good service in accordance with the wishes of the community library users. Various service activities conducted by the library are all intended for the use of library materials and facilities owned by the library. Keywords: activities, services, search, information